Enhancing Document Digitization: The All-in-One ‘Document World’ App: for Scanning and Editing PDFs with QR Code Support - Kadam, Tanmay; Jathar, Akash; Bhiugade, Pratosh; Parab, Darshan; Shivsharan, Nitin (INFOCOMP Journal of Computer Science, 2024)
The aim of this article is to provide assistance to students, employees, and the general public through the use of document scanning, Optical Character Recognition (OCR), QR generation, and QR reading. With the increasing trend of digitalization in educational institutions, offices, and governments, there is a constant need for tools that can help us accomplish these tasks. To facilitate this process, we require a reliable scanning app with features like PDF tools, QR generator, and QR reader. While numerous apps are available online, they often lack in quality and some functions, or require payment for advanced features. However, the “Documents World App” provides a solution with its quality scanning, PDF tool options for modifying existing PDFs, and editing options for adding signatures and watermarks, which simplifies our work. This app offers advanced functionalities, such as text extraction with the help of the itext library, that are not typically available in widely used tools like ”Adobe Scan” and ”iLove PDF”. Furthermore, we aim to provide this service to all users without any charge and the add free.